2020
DOI: 10.1002/mdc3.12883
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐Negative Paraneoplastic Limbic Encephalitis, Parkinsonism, Hypothermia, and Narcolepsy Associated with Endometrial Carcinoma

Abstract: Background Background: We describe the clinical and neuropathological features of a patient with T-cellmediated paraneoplastic limbic encephalitis, parkinsonism, hypothermia, and narcolepsy-like presentation associated with endometrial carcinoma. Objectives Objectives: This patient with prominent parkinsonism and narcolepsy broadens the phenotype of known paraneoplastic syndromes and demonstrates the importance of investigation for occult malignancy even in the absence of paraneoplastic antibodies. Methods Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Novel antibodies related to paraneoplastic syndromes should be studied or reported and can not be ruled out as suggested by authors [15] appeared to be suitable and efficient instruments for assessing HRQoL in PWN [30]. Chang., et al in their case control study reported significantly increased risk of narcolepsy patients to burn injury compared to unaffected controls.…”
Section: Current Updatesmentioning
confidence: 99%
“…Novel antibodies related to paraneoplastic syndromes should be studied or reported and can not be ruled out as suggested by authors [15] appeared to be suitable and efficient instruments for assessing HRQoL in PWN [30]. Chang., et al in their case control study reported significantly increased risk of narcolepsy patients to burn injury compared to unaffected controls.…”
Section: Current Updatesmentioning
confidence: 99%